Sensitivity Analysis of Price Indices in Models of Demand Systems - Renata Benda-Prokeinová; Martina Hanová; Natalia Turčeková (Statistika: Statistics and Economy Journal, 2021)
The primary motivation of the paper is to point out the sensitivity of price indices calculated by the model of demand systems in different price and quantitative levels. We simulated different prices and quantities, so increasing the values of the variables reduced their variance. We would like to point out the significant role of variability and thus the deviation of input data, which is the basis for identifying consumer behavior. From the methodology, we used the Linearized Almost Ideal Demand System and focused on the partial output of specific expenditure elasticities calculated by price indices – Stone, Laspeyres and Törnqvist index. Following we are wondering which index can consider as the most trustworthy? In the analysis, we realized that the price variance would affect the indices' values more significantly, than the more considerable variance of the quantity consumed. It means that elasticities characterize consumer behavior in terms of prices, not in terms of quantity consumed.